EVALUASI MODEL CIPP EKSTRAKURIKULER ECOPRINT DENGAN TEKNIK STEAMING DI PKBM TIM SUARA MASYARAKAT DAWUAN CIKAMPEK - Nurangriani, Leni (IKIP Siliwangi, 2025)
This study aims to evaluate the implementation of the ecoprint extracurricular program with the steaming technique at the Dawuan Community Voice Team (TSMD) Community Learning Activity Center using the CIPP (Context, Input, Process, Product) evaluation model. This program is designed as part of life skills education that integrates aspects of skills, environment, and community empowerment. The research approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the evaluation on the context aspect show that the suitability of the program to the needs of the students, the relevance of the program to educational policies and the surrounding environment, clear and measurable program targets and objectives. On the input aspect, the program has involved the qualifications and competencies of teaching staff/instructors, the availability of supporting facilities and infrastructure, the curriculum and learning methods used, funding sources, program sustainability, and the time and place of implementation. The process aspect shows the implementation of activities according to plan, the level of involvement and activeness of learners, the teaching and guidance methods applied, the obstacles faced during the program, evaluation and monitoring during the program. Meanwhile, in the product aspect, improving the skills of learners, improving the attitudes of learners, improving the knowledge of learners, the quality of products produced in the program, the impact of the program on the independence of learners and related stakeholders, and the sustainability and potential for program development. This evaluation concludes that the ecoprint program at PKBM TSMD has a positive impact and sustainable potential, although it needs improvement in terms of supporting facilities and a more stable funding system.